Evaluación de la aplicación de beneficios tributarios de impuesto a la renta en una institución sin fines de lucro - Parra Cajamarca, Emanuel Fernando (2015)
The tax benefits that the state grants to the various companies such as the exemption of income tax and the exemptions that enjoy the not-for-profit institutions such as the drew Villanueva, Rivas, Ávila, Red your paper exemptions and tax exemptions in Nicaragua published in 2014 will be employed through concepts and rules of diagnosis that will serve to identify the problem that has the Union of Cantonal professional drivers of passage. The methodology to be deployed into the research project is qualitative because it allows a strategy to try to know the facts, structures and people in their entirety and not through the measurement of certain elements, the collection technique that is employment data will be the guide of observation, and the interview, we also will use the method descriptive, analytical and scientific observation. You can make the description of the proposal that is going to pose to resolve the problems which are hosts to the institution, the goal that has the integrating project is to establish a procedure by applying the legal regulations related to tax non-profit institutions to request values paid in excess or unduly to the tax administration. Reached a favorable outcome for the institution as it will allow you to recover balance to favor in the hands of the state as well be able to reinvest in their own institution and able to provide to partners and customers services more comfortable. The third chapter will indicate the form of technical analysis, economic, social and environmental conditions. It will be possible to know what is the impact that will cause our integrative approach with each of them. A recommendation for the institution is that it does not accumulate so much money in the hands of the state since that money is not generating any benefit to the institution.